Some recent German fairy tales: a translation - Brink, Raymond Woodard (My University, 1908)
Introduction: A short time ago, the “Woche”, one of the leading German weekly papers, offered prized for the best fairy tales. The thirty best stories were to be published in a book called “Neuer deutscher Marchenschatz”, and the authors were each to receive a hundred marks.
Citation: Brink, Raymond Woodard. Some recent German fairy tales: a translation. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fairy Tales; German Literature; Translations; Graduating theses; Senior theses; Theses